Use of Information Technology on Students' Physical Activity - Lutfiyani, Anisa; Anggoro, Tri; Santoso, Rahmawan; Wijaya, Febri (Champions: Education Journal of Sport, Health, and Recreation, 2024)
Physical activity is very important for human health in carrying out daily activities. Sedentary activities caused by playing online or offline games too often, internet, watching television too much will result in the risk of obesity. Overweight is considered a risk factor for various diseases, such as diabetes, heart disease, hypertension and many others. This study aims to determine whether there is an influence and how much information technology users on students' physical activity at SMA Negeri 3 Slawi. This research uses a quantitative approach through correlation techniques and correlation methods. The subjects in this study were class X students of SMA Negeri 3 Slawi using cluster random sampling consisting of 27 classes with a total population of 558 students categorized as 257 male students and 278 female students. And from the results of cluster random sampling obtained 5 classes with a total sample of 150 students. The data analyzed in this study were Descriptive analysis and Inferential analysis. The results showed that there was a significant correlation between the use of technology (X) and physical activity (Y). This can be proven by the correlation coefficient value (Ry1) = 0.133 with the regression equation y ̂ = 6.123 + 0.007 X. The coefficient of determination shows that r2 = (0.113)2 = 0.176, meaning 17.6%. Physical activity is influenced by the use of technology, so this study concludes that there is a relationship between the use of technology and physical activity.